Pembiayaan Syariah Pada ESCO Dalam Menunjang Efisiensi Energi - Aulia, Rizki; Sammaranta Siregar, Theo; Puji Agustin, Yuda (UI Scholars Hub, 2025)
Climate change and the need to reduce energy consumption make energy efficiency an important solution to achieve sustainability. Energy Services Companies (ESCOs) play a central role in the implementation of energy efficiency technologies through various services such as consulting, project development, and verification of energy savings. However, one of the main challenges in this implementation is the need for significant initial investment, which is often an obstacle for project owners, especially in developing countries where high financial risk is a major obstacle. Islamic financing, based on the principles of Islamic law, offers an attractive alternative to overcome such challenges. The key principles of Islamic financing, such as the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling), emphasise the value of fairness and transparency in financial management. The method used in this research is doctrinal research method by analysing and evaluating legal provisions, regulations, and applicable legal principles related to the dynamics of Islamic financing in Energy Service Company (ESCO) in supporting energy efficiency. The results show that in the context of ESCOs, Islamic financing can be applied through two main business patterns, namely ‘guaranteed energy savings’ and ‘shared energy savings.’ Under the ‘guaranteed energy savings’ scheme, the ESCO guarantees certain energy savings to the project owner. If the savings do not reach the promised target, the ESCO will bear the loss, in line with Shariah principles that promote a mutually beneficial relationship. The ‘shared energy savings’ pattern allows the ESCO and the project owner to share the risks as well as the returns from the achieved energy savings. The advantage of Islamic financing in this context lies in its ability to overcome capital barriers, expand access to more diverse financing, and increase the attractiveness of ESCOs, especially in developing countries.